Hovercraft trials in the Mackenzie River delta, 1966 - Cooper, P. F.; Storr, J. W. (Polar Record, 1967)
Hovercraft, or air-cushion vehicles, have been proposed several times as a means of polar transport (Mellor, 1963; Fuchs, 1964, 1966; Law, 1965; Cooper, 1965). They ride on a cushion of low pressure air which eliminates friction between the craft and the ground surface, the air being contained by flexible skirts and peripheral jets to give a substantial obstacle clearance. Their low bearing pressure (of the order of 0·01 kg/cm 2 ) makes them potentially suitable for over-snow use. They can travel equally well over ice, snow, and water and thus can give year-round service on Arctic rivers and seas. There is no need for costly facilities such as docks or airstrips at terminals. Finally, the hard structure clearance provided by the flexible skirts should enable the vehicle to cross areas of rough sea ice or pressure ridges without a route being prepared.